Forensic dental identification of remains in five prefectures in the Kansai region of Japan. Issue 1 (21st October 2019) - Ichioka, Hiroaki; Bando, Risa; Tsuboi, Hajime; Idota, Nozomi; Kumagai, Wataru; Ikegaya, Hiroshi
Abstract: The numbers of forensic dental analyses and police dentists performing the analyses differ among the prefectures in Japan. Very little is known about the numbers of these analyses and the processes used to enlist dental experts. This report investigated the method of assigning police dentists for identification of the remains, number of the dentists, number of assigned dental analyses, payment for dental services, etc in five prefectures in the Kansai region. The number of studied remains, dental analyses, and identification by the dental experts annually processed by prefectural police stations in 2015, 2016, and 2017 are summarized. The number of the dental analyses in the five prefectures in the Kansai region ranged from 0.3 to 2.3 per 100 recovered remains, which is considered low. There was no relationship between the number of the dental analyses performed and the number of the police dentists. Utilizing the results from this report enables the creation of a database to establish better systems for forensic dentistry, which will enable a larger number of the dental analyses and earlier and accurate identification of unidentified remains.